A rheological and spectroscopic study on the kinetics of self‐healing in a single‐component diels–alder copolymer and its underlying chemical reaction. Issue 12 (1st April 2014) - Bose, Ranjita K.; Kötteritzsch, Julia; Garcia, Santiago J.; Hager, Martin D.; Schubert, Ulrich S.; van der Zwaag, Sybrand
ABSTRACT In this work, pendant groups with both furan and maleimide moieties were incorporated into a polymethacrylate copolymer with lauryl methacrylate as comonomer to yield a one‐system Diels–Alder (DA) polymer. A combined Fourier transform infrared (FTIR) spectroscopy and rheological study was performed to quantify the extent of the reversible DA reaction and the resulting changes in mechanical properties of the polymer. The kinetics of the retro‐Diels–Alder (rDA) reaction was studied at different temperatures to determine an enthalpy of activation. Control polymers with only one functional moiety, that is, the furan or maleimide, were also synthesized to study the differences in viscoelastic behavior and the absence of self‐healing. Microscratch tests were performed to obtain information about the disappearance of well‐defined intentional surface scratches under different healing conditions. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1669–1675